Analysis Of The Effect Of Economic Growth, Open Unemployment Rate, Human Development Index On The Number Of Poor People In Sumatra Island Using Panel Data - Marita Damanik; M. Syafii; Irsyad Lubis (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The purpose of this study is to analyze the effect of economic growth, open unemployment rate, and Human Development Index on the number of poor people on the island of Sumatra both partially and simultaneously. This type of research is quantitative research and the data in this study are secondary data from the period 2012 - 2021 sourced from the Central Bureau of Statistics and using panel data analysis techniques. The results of the study are that economic growth has an effect and is not significant on the number of poor people on the island of Sumatra, the open unemployment rate has an effect and is significant on the number of poor people on the island of Sumatra, the human development index has no effect on the number of poor people on the island of Sumatra. Simultaneously, economic growth, open unemployment rate, and human development index have a significant effect on the number of poor people on the island of Sumatra.